Kajian Revegetasi Pada Aktivitas Reklamasi Lahan Bekas Tambang Batubara: Revegetation Study on Reclamation Activities of Former Coal Mine Land - Nurwaskito, Arif; Akbar, Muhammad; Thamsi, Alam Budiman; Aswadi, Muhammad (CV Insight Publisher, 2024)
Before carrying out mining, it must take into account the impact of mining activities, namely changes in the landscape, it is necessary to re-vegetate and replant. This research was conducted to find out and provide a solution to the problem of revegetation failure that often occurs to achieve revegetation success and to identify and improve the factors that cause many dead plants. The location of this research was conducted in Bantuas Village, Palarang District, Samarinda Municipality, East Kalimantan Province, the data collection technique was carried out by direct collection in the field by taking data on plant types and soil pH, data processing was carried out by processing the collected data by entering data into in excel software aims to make the data neatly arranged and the data analysis method used is qualitative. There are several factors that cause plants to die, namely due to an error in selecting plant species and not paying attention to acidic soil pH. The way to overcome this is by choosing plant types that are suitable for the revegetation area and using dolomite to neutralize acidic soil pH and to achieve success it is necessary to pay attention to plant types, maintenance, planting preparation, monitoring.